KUALITAS PEMBANGUNAN MANUSIA PULAU NIAS SEBAGAI PERWUJUDAN TUJUAN PEMBANGUNAN MANUSIA BERKELANJUTAN - Bangun, Rita Herawaty (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2020)
The purpose of the research is to look at the achievements of human development on Nias Island from its three constituent aspects namely health, education and income. Based on an analysis of the three aspects of the HDI compilers, the quality of human development on Nias Island during the period of 2014 to 2018 showed an increase. This research uses descriptive analysis techniques using secondary data. The results also show that there is still a disparity in human development between regions on Nias Island. The human development of Gunungsitoli City is better compared to other regions. This is influenced by regional factors, infrastructure, and easy access to reach aspects of life such as education facilities and health facilities. To further improve human quality and reduce disparities between regions, the Sumatera Utara Provincial Government needs to make policy programs especially in the aspects of Education and health aspects. Institutional strengthening and infrastructure development to support economic growth for fair and equitable welfare for all people on Nias Island.